Observation of Six Pre-Flare VLP Pulsations in Solar Corona - Malihe Jalalirad; Narges Fathalian (Iranian Journal of Astronomy and Astrophysics, 2023)
Solar flares are sudden bursts in the solar atmosphere, which emit from radio wavelengths to gamma rays, and according to their energy, are classified into different classes (A, B, C, M, and X, respectively). Predicting the time of the flare occurrence and determining its class type can help reduce its destructive effects. One of the observable structures that can be seen before a flare occurs are oscillations with very long period pulsations (VLPs) of the order of 8-30 minutes, which occur about one to two hours before the flare onset. In this paper, using GOES data, we observed typical VLPs before flare-onset for six flares in Class C and M. Periodicities that we calculated for the VLPs of these flares are between 14.6 and 28.2 minutes, which is in agreement with the results of Tan et al. (2016). The number of pulses observed in each pre-flare is between 4 and 6. For the other two remaining flares of our selection, no typical pre-flare VLP was observed.